We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
63
2
avatar+1028 

The red parabola shown is the graph of the equation \(x = ay^2 + by + c\). Find \(a+b+c\).

 

 Jul 15, 2019
 #1
avatar+22892 
+2

The red parabola shown is the graph of the equation \(x = ay^2 + by + c\)

Find \(a+b+c\).

 

The Vertex of the parabola is \(P(x=-3,\ y=1)\)

\(\begin{array}{|rcll|} \hline \mathbf{ay^2 + by + c} &=& \mathbf{x} \quad | \quad x=-3,\ y=1 \\\\ a*(1)^2 + b*(1) + c &=& -3 \\ \mathbf{a + b + c} &=& \mathbf{-3} \\ \hline \end{array}\)

 

laugh

 Jul 15, 2019
 #2
avatar+18754 
+2

Start with the vertex form     x = a(y-k)^2 + h

where h, k is the vertex

 

x = a (y-1)^2 -3    Substitute a value from the graph to find a     use  -2, 2

-2 = a(2-1)^2 -3

a = 1

so your equation for the parabola is   x = (y-1)^2 -3    now expand the right side

x = y^2 - 2y+1   -3

x = y^2 - 2y -2      a =1   b = -2   c = -2      sum = -3

 Jul 15, 2019

17 Online Users

avatar